Molecular characterization and classification of Trypanosoma spp. Venezuelan isolates based on microsatellite markers and kinetoplast maxicircle genes. Issue 1 (December 2015) - Sánchez, E.; Perrone, T.; Recchimuzzi, G.; Cardozo, I.; Biteau, N.; Aso, PM; Mijares, A.; Baltz, T.; Berthier, D.; Balzano-Nogueira, L.; Gonzatti, MI
Abstract Background Livestock trypanosomoses, caused by three species of the Trypanozoon subgenus, Trypanosoma brucei brucei, T. evansi andT. equiperdum is widely distributed throughout the world and constitutes an important limitation for the production of animal protein.T. evansi andT. equiperdum are morphologically indistinguishable parasites that evolved from a common ancestor but acquired important biological differences, including host range, mode of transmission, distribution, clinical symptoms and pathogenicity. At a molecular level, T. evansi is characterized by the complete loss of the maxicircles of the kinetoplastic DNA, whileT. equiperdum has retained maxicircle fragments similar to those present inT. brucei. T. evansi causes the disease known as Surra, Derrengadera or "mal de cadeiras", whileT. equiperdum is the etiological agent of dourine or "mal du coit", characterized by venereal transmission and white patches in the genitalia. Methods Nine VenezuelanTrypanosoma spp . isolates, from horse, donkey or capybara were genotyped and classified using microsatellite analyses and maxicircle genes. The variables from the microsatellite data and the Procyclin PE repeats matrices were combined using the Hill-Smith method and compared to a group ofT. evansi, T. equiperdum andT. brucei reference strains from South America, Asia and Africa using Coinertia analysis. Four maxicircle genes (cytb, cox1, a6 and nd8) were amplified by PCRfrom TeAp-N/D1 and TeGu-N/D1, the two Venezuelan isolates that grouped with the T.equiperdum STIB841/OVI strain. These maxicircle sequences were analyzed by nucleotide BLAST and aligned toorthologous genes from the Trypanozoon subgenus by MUSCLE tools. Phylogenetic trees were constructed using Maximum Parsimony (MP) and Maximum Likelihood (ML) with the MEGA5.1® software. Results We characterized microsatellite markers and Procyclin PE repeats of nine VenezuelanTrypanosoma spp. isolates with various degrees of virulence in a mouse model, and compared them to a panel ofT. evansi andT. equiperdum reference strains. Coinertia analysis of the combined repeats and previously reportedT. brucei brucei microsatellite genotypes revealed three distinct groups. Seven of the Venezuelan isolates grouped with globally distributedT. evansi strains, while TeAp-N/D1 and TeGu-N/D1 strains clustered in a separate group with theT. equiperdum STIB841/OVI strain isolated in South Africa. A third group includedT. brucei brucei, two strains previously classified asT. evansi (GX and TC) and one asT. equiperdum (BoTat-1.1). Four maxicircle genes, Cytochrome b, Cythocrome Oxidase subunit 1, ATP synthase subunit 6 and NADH dehydrogenase subunit 8, were identified in the two Venezuelan strains clustering with theT. equiperdum STIB841/OVI strain. Phylogenetic analysis of thecox1 gene sequences further separated these two VenezuelanT. equiperdum strains: TeAp-N/D1 grouped withT. equiperdum strain STIB818 andT. brucei brucei, and TeGu-N/D1 with theT. equiperdum STIB841/OVI strain. Conclusion Based on the Coinertia analysis and maxicircle gene sequence phylogeny, TeAp-N/D1 and TeGu-N/D1 constitute the first confirmedT. equiperdum strains described from Latin America.